Converting Brownmillerite to Alternate Layers of Oxygen‐Deficient and Conductive Nano‐Sheets with Enhanced Thermoelectric Properties. Issue 28 (11th June 2022) - Hu, Songbai; Han, Wenqiao; Li, Xiaowen; Ye, Mao; Lu, Yao; Jin, Cai; Liu, Qi; Wang, Junling; He, Jiaqing; Cazorla, Claudio; Zhu, Yuanmin; Chen, Lang
Abstract: Introducing large oxygen deficiencies while retaining low resistivity is important for enhancing the overall thermoelectric properties in 3d transition‐metal oxides. In this study, a new synthesis route to reconstruct the insulating brownmillerite SrCoO2.5 is adapted. Through a step‐by‐step nano‐blocks modification, a series of highly‐conductive layered structures is evolved, which are [Sr2 O2 H2 ]0.5 CoO2, [Sr2 O2 ]0.4 CoO2, and [Sr2 CoO3 ]0.57 CoO2, while still retaining considerable Seebeck coefficient (≈ 100 µ V K −1 ). Coexistence of low resistivity and high oxygen deficiency is realized in the latter two polymorphs by forming a majority of sintered oxygen vacancies in the rock‐salt layer and a minority of normal oxygen vacancies in the CoO2 layer. A room‐temperature in‐plane power factor of 3.6 mW K −2  m −1, power output density of 4.5 W m −2 at a temperature difference of 28 K, and an out‐of‐plane thermal conductivity of 0.33 W K −1  m −1 are obtained in the [Sr2 O2 ]0.4 CoO2 thin film that exhibits the highest oxygen deficiency (δ =  2.95), which is on par with Bi2 Te3, the benchmark. It is pointed out that proper distribution of oxygen vacancy is essential in tailoring the physical and chemical properties of transition‐metal oxides. The sintered/normal oxygen vacancy layer model provides guidance to the exploration of materials with both low electric resistivity and thermal conductivity. Abstract : Thermoelectric‐poor brownmillerite SrCoO2.5 is converted to a [Sr2 O2 H2 ]0.5 CoO2, [Sr2 O2 ]0.4 CoO2 and [Sr2 CoO3 ]0.57 CoO2 layered‐structure. A room‐temperature in‐plane power factor of 3.6 mW K −2  m −1, power output density of 4.5 W m −2 at temperature diffence of 28 K and out‐of‐plane thermal conductivity of 0.33 W K −1 m −1 are obtained in the [Sr2 O2 ]0.4 CoO2 that exhibits the highest oxygen deficiency (δ = 2.95), which is on par with Bi2 Te3, the benchmark.